The Influence of Leadership Style, Discipline and Work Environment on Performance with Work Motivation as a Mediator for MtsN 3 Banyuwangi Teachers and Education Staff - Aneka Sulastri; Yuniorita Indah Handayani; Dedy Wijaya Kusuma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The performance of educators and education personnel is a key factor in determining student success and the reputation of educational institutions. This study aims to analyze the influence of leadership style, work discipline, and work environment on work motivation and performance among educators and education personnel at MTsN 3 Banyuwangi. Additionally, it examines the role of work motivation as a mediating variable in the relationship between leadership style, work discipline, and work environment with performance. This study employs a quantitative approach, collecting data through questionnaires distributed to 87 respondents, consisting of educators and education personnel at MTsN 3 Banyuwangi. Data analysis is conducted using path analysis with the assistance of SmartPLS V3 software. The findings reveal that leadership style, work discipline, and work environment each have a direct impact on work motivation. Furthermore, these factors also directly influence performance. Work motivation itself significantly affects performance. However, the indirect influence of leadership style, work discipline, and work environment on performance through work motivation as a mediator is not significant. Thus, this study concludes that leadership style, work discipline, and work environment play a crucial role in directly enhancing the motivation and performance of educators and education personnel. Therefore, direct management of these factors should be a top priority in improving performance at MTsN 3 Banyuwangi.